A comprehensive framework to assess the sustainability of nutrient use in global livestock supply chains - Uwizeye, Aimable; Gerber, Pierre J.; Schulte, Rogier P.O.; de Boer, Imke J.M. (Journal of cleaner production, 2016)
The assessment of the performance of nutrient use along livestock supply chains can help to identify targeted nutrient management interventions, with a goal to benchmark and to monitor the improvement of production practices. It is necessary, therefore, to develop indicators that are capable to describe all nutrient dynamics and management along the chain. This paper proposed a comprehensive framework, based on life-cycle thinking, to assess the sustainability of nitrogen and phosphorus use. The proposed framework represents nutrient flows in typical livestock supply chain from the “cradle-to-primary-processing-gate”, including crop/pasture production, animal production, and primary processing stage as well as the transportation of feed materials, live-animals or animal products. In addition, three indicators, including the life-cycle nutrient use efficiency (life-cycle-NUE), life-cycle net nutrient balance (life-cycle-NNB) and nutrient hotspot index (NHI) were proposed and tested in a case study of mixed dairy supply chains in Europe. Proposed indicators were found to be suitable to describe different aspects of nitrogen and phosphorus dynamics and, therefore, were all needed. Moreover, the disaggregation of life-cycle-NUE and life-cycle-NNB has been investigated and the uncertainties related to the choice of the method used to estimate changes in nutrient soil stock have been discussed. Given these uncertainties, the choice of method to compute the proposed indicators is determined by data availability and by the goal and scope of the exercise. •We test a framework to assess the performance of nutrient use in livestock systems.•The framework accounts for more nutrient processes, pools and end-uses.•We propose three indicators required to describe nutrient dynamics and performance.•The framework is sensitive to methods selected to estimate nutrient stock change.